One step development of high entropy alloy for high performance supercapacitors electrodes - Liao, Yiyu (Nanyang Technological University, 2023)
Supercapacitor plays a crucial role in energy storage application, relying on its superior electrochemical performance, which is mainly determined by the electrode material used. Research on alternatives for pure carbon as the electrodes in the electric double-layer capacitor (EDLC) are carried out continuously in recent years, one typical solution is the utilization of High-entropy alloys (HEAs). HEAs are a relatively new class of materials that consist of multiple metallic elements in roughly equal proportions, which exhibit unique properties mechanically, electrically, and chemically. This project aims to synthesize an asymmetric solid supercapacitor using high-entropy alloy nanoparticles (HEA-NPs) decorated carbon cloth and an active carbon paper. The HEA-NPs consisted of 5 metallic elements: Chromium, Cobalt, Nickle, Manganese, and Zinc (CrCoNiMgZn) were synthesized on the carbon cloth using a pulsed laser irradiation (PLI) method, resulting in a highly conductive and porous nanocomposite electrode. The electrochemical performance of the HEA/carbon electrode was characterized, showing expected specific capacitance, superior rate capability as well as promising cycling stability. Lastly, the limitations of the study were identified, and recommendations for further exploration were suggested. This project is to provide a reference for the synthesis of HEA-NPs using PLI, insights into alternatives for electrode materials of EDLC, as well as the potentiality of HEA-NPs in sustainable energy storage applications.